2020
DOI: 10.1101/2020.06.05.136341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-particle cryo-EM refinement withMvisualizes ribosome-antibiotic complex at 3.7 Å inside cells

Abstract: Cryo-electron microscopy (cryo-EM) enables macromolecular structure determination in vitro and in situ. In addition to aligning individual particles, accurate registration of sample motion and 3D deformation during exposures is crucial for achieving high resolution. Here we describe M, a software tool that establishes a reference-based, multi-particle refinement framework for cryo-EM data and improves the results of structure determination. M provides a unified optimization framework for both in vitro frame se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 50 publications
0
60
0
Order By: Relevance
“…During the experiment setup, there is a natural urge to use higher defocus because it makes the molecules of the sample easier to see in the images. However, during processing, strongly delocalized high-resolution signals require more care and are more difficult to recover (Tegunov et al, 2020). Our experience showed that using lower defocus values, and the associated much lower image contrast, did not lessen the ability to locate and accurately align the particles during reconstruction.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…During the experiment setup, there is a natural urge to use higher defocus because it makes the molecules of the sample easier to see in the images. However, during processing, strongly delocalized high-resolution signals require more care and are more difficult to recover (Tegunov et al, 2020). Our experience showed that using lower defocus values, and the associated much lower image contrast, did not lessen the ability to locate and accurately align the particles during reconstruction.…”
Section: Resultsmentioning
confidence: 82%
“…Current particle handling strategies in the most popular image processing packages impose a restriction on the minimum particle box size as a function of the maximum defocus in the dataset that will preserve delocalized high-resolution components within the box. The recently introduced M package overcomes this limitation by performing a CTF sign correction on a larger area before extracting the particle box (Tegunov et al, 2020). This was shown to solve the resolution limitation of higher defocus values and could allow their use in the future without detrimental effects.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these technical challenges, recent successes in cryo-ET of noncrystalline specimens support applying this technique to solve structures from nanocrystals to high resolution. In particular, subtomogram averages of purified immature HIV-1 Gag particles to 3.1Å and in situ ribosomes to 3.7Å demonstrate that high-resolution signal is available in tilt-series data [20,21]. As with SPR, only particles with high molecular weight can be aligned with sufficient accuracy for this high-resolution information to be retained during subtomogram averag-ing.…”
Section: Discussionmentioning
confidence: 96%
“…While the use of nanocrystals facilitates determining relative particle orientations, the low molecular weight of the constituent proteins makes finding a common phase origin -the other step of particle alignment -more challenging. High-resolution subtomogram averaging has exclusively targeted high molecular weight proteins, and with two exceptions, isolated particles in solvent [19][20][21]70]. These characteristics facilitate finding a common phase origin from each particle's center of mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation